Neandertals and Modern Humans in Western Asia
XI, 539 p. 61 illus.
Keywords: In this fascinating volume, the Middle Paleolithic archaeology of the Middle East is brought to the current debate on the origins of modern humans. These collected papers gather the most up-to-date archaeological discoveries of Western Asia - a region that is often overshadowed by African or European findings - but the only region in the world where both Neandertal and early modern human fossils have been found. The collection includes reports on such well known cave sites as Kebara, Hayonim, and Qafzeh, among others. The information and interpretations available here are a must for any serious researcher or student of anthropology or human evolution.